2021
DOI: 10.1021/acs.jpca.0c10544
|View full text |Cite
|
Sign up to set email alerts
|

Elusive Magnetic Compounds Originated from Planar Tetracoordinate Silicon, a Theoretical Prediction

Abstract: A family of novel compounds with planar tetracoordinate silicon (ptSi) supported by B-heterocyclic carbenes (BHCs) have been theoretically investigated. The lowest energy molecules (a3, b3, and c3) with single ptSi are a triplet. We further designed 1D and 2D compounds with multi-ptSi atoms by condensation of a3 along latitudinal (m) and longitudinal (n) directions. The lowest energy 1D compounds prefer to be zigzag conformation along the m direction. The lowest energy 2D compounds (m,n) (m ≥ n) are zigzag con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…16,17 Strategies to stabilize square planar congurations for some other elements were probed computationally, [18][19][20][21][22][23][24] and substantial progress was made for compounds featuring planar silicon. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] However, a systematic fundament of the inversion process in ER 4 compounds or more general statements on their tetrahedral preference are elusive. This lack appears surprising compared with the extensive knowledge on the inversion process of trigonal group 15 compounds ER 3 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Strategies to stabilize square planar congurations for some other elements were probed computationally, [18][19][20][21][22][23][24] and substantial progress was made for compounds featuring planar silicon. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] However, a systematic fundament of the inversion process in ER 4 compounds or more general statements on their tetrahedral preference are elusive. This lack appears surprising compared with the extensive knowledge on the inversion process of trigonal group 15 compounds ER 3 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Additionally, BHCs were recently used to design porous organic molecules (POMs) 39 and stabilize planar tetracoordinate silicon (ptSi). 40 Inspired by the recent work reported by Li et al, who found that SiH 2 can stabilize CN bond to produce 1-aza-2,4-disilabicyclo[1,1,0]butanes, 41 we anticipated obtaining a family of novel molecules X 2 SiC 2 BR given by the substitution of SiX 2 for the CX 2 unit in BHCs. As such, a type of novel carbene, (Si and B)-heterocyclic carbenes (SiBHCs), was anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Additionally, BHCs were recently used to design porous organic molecules (POMs) 39 and stabilize planar tetracoordinate silicon (ptSi). 40…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, calix[4]­pyrrole hydridosilicate, the first nonmetal molecule with ptSi, was successfully synthesized experimentally . In 2021, Zhang et al proposed a series of novel compounds with ptSi supported by B-heterocyclic carbenes (BHCs) through theoretical study . In the same year, a variety of compounds containing anti-van’t Hoff/Le Bel ptSi were successfully synthesized, exhibiting remarkable stability at room temperature .…”
mentioning
confidence: 99%
“…18 In 2021, Zhang et al proposed a series of novel compounds with ptSi supported by B-heterocyclic carbenes (BHCs) through theoretical study. 19 In the same year, a variety of compounds containing anti-van't Hoff/Le Bel ptSi were successfully synthesized, exhibiting remarkable stability at room temperature. 20 Just recently in 2023, Shan et al reported the first experimental synthesis of isolable metalfree ptSi(II) dication.…”
mentioning
confidence: 99%